Studi Pengelolaan Air Bersih Pamsimas di Desa Wukirsawit Kecamatan Jatiyoso Kabupaten Karanganyar - Priaji Agung Dewantoro; Ana Khoirul Ummah; Aprin Wahyu Wijayanti; Ana Yustika (STIKES HAKLI Semarang, 2025)
Water is an important environmental component for the life of living beings. Therefore, the availability of water needs to be studied both in terms of quantity and quality. The Community-Based Drinking Water and Sanitation Provision Program (PAMSIMAS) in the Wukirsawit Village area, Jatiyoso District, Karanganyar Regency emerged due to the encouragement of the urgent needs of the local community for access to clean water and proper sanitation. This type of research is descriptive research, which is research that aims to describe clean water management in the implementation of the PAMSIMAS program in Wukirsawit Village in 2024, including to determine the quality of clean water produced. Data collection techniques were carried out through structured interviews, direct observations, questionnaires, clean water quality tests, and documentation. Data analysis was carried out by referring to the Regulation of the Minister of Health of the Republic of Indonesia Number 32 of 2017 concerning Environmental Health Quality Standards and Water Health Requirements for the Purposes of Hygiene Sanitation, Swimming Pools, Solus Per Aqua, and Public Baths. The PAMSIMAS clean water management that has been implemented includes several aspects, namely organizing, maintaining, supplying, types of clean water facilities, fulfilling clean water aspects, and checking water quality. The results of the assessment of the achievement of the PAMSIMAS program for each aspect in a row, namely 88%, 80%, 70%, 75%, 60%, and 75%. These findings show that the PAMSIMAS program in Wukirsawit Village has provided real benefits in increasing community access to clean water. However, continuous efforts are still needed in terms of maintaining facilities, equitable distribution of water supply, and improving quality so that the program can be more optimal and sustainable.